Bacterial cytoplasm as an effective cell compartment for producing functional VHH-based affinity reagents and Camelidae IgG-like recombinant antibodies - Djender, Selma (BioMed Central, 2014)
BACKGROUND: The isolation of recombinant antibody fragments from displayed libraries represents a powerful alternative to the generation of IgGs using hybridoma technology. The selected antibody fragments can then be easily engineered into (multi)-tagged constructs of variable mass and complexity as well as reconstituted into Camelidae IgG-like molecules when expressed fused to Fc domains. Nevertheless, all antibody constructs depend on an oxidizing environment for correct folding and consequently still belong to the proteins difficult to express in bacteria. In such organisms they are mostly produced at low yields in the periplasmic space. RESULTS: We demonstrate that fusion constructs of recombinant antibodies in combination with multiple tags can be produced at high yields and totally functional in the cytoplasm of bacteria expressing sulfhydryl oxidase. The method was applied to structurally demanding molecules such as VHHs fused to SNAP and Fc domains and was validated using the antibody-derived reagents in a variety of immune techniques (FACS, ELISA, WB, IP, SPR, and IF). CONCLUSIONS: The collected data demonstrate the feasibility of a method that establishes a totally new approach for producing rapidly and inexpensively functional Camelidae IgG-like monoclonal antibodies and antibody-based reagents containing multiple disulfide bonds and suitable for both basic research and clinical applications. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12934-014-0140-1) contains supplementary material, which is available to authorized users.